Impact of income redistribution on middle class households: A cross-country comparison based on the LIS data - Régis Bigot; Emilie Daudey; Jörg Muller; Guillaume Osier (Luxembourg Income Study (LIS), 2014)
In the context of economic and financial difficulties, the debate over the effect of income taxation and redistribution has come back in most of the European countries. In this paper, we use the LIS data to examine the impact of income redistribution on middle class households from a cross-country perspective. To this aim, we calculate the balance between, on the one hand, the taxes and social contributions those households have to pay and, on the other, what they receive as social transfers. The research question here is whether middle class households benefit more or less from income redistribution than lower and upper class households. According to this study, income redistribution schemes appear to be "redistributive" in most of the European countries, which means that households having high income contribute to the income of those having lower resources. However, the intensity of the redistribution varies from one country to another: basically, northern European countries, in line with the Beveridge "universal" approach are more redistributive than southern countries, where social protection is mainly financed by employers and employee social insurance contributions.
Keywords: 330